2007
DOI: 10.1111/j.1469-8137.2007.02141.x
|View full text |Cite
|
Sign up to set email alerts
|

Truffle volatiles inhibit growth and induce an oxidative burst in Arabidopsis thaliana

Abstract: Summary• The function of fungal volatiles in fungal-plant interactions is poorly understood. The aim here was to address this lack of knowledge, focusing on truffles, ectomycorrhizal fungi that are highly appreciated for their aroma.• The effect of volatiles released by truffles was tested on Arabidopsis thaliana in a closed chamber bioassay. The volatiles produced by Tuber melanosporum , Tuber indicum and Tuber borchii fruiting bodies inhibited A. thaliana in terms of root length and cotyledon leaf size, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
126
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(133 citation statements)
references
References 25 publications
5
126
0
2
Order By: Relevance
“…A close correlation between infection in herbaceous plant roots and Tubermelanosporum was observed by Plattner & Hall (1995), who demonstrated that T. melanosporum caused necrosis in the root cortices of Anthoxanthum odoratum, and Leontodon taraxacoides, thus suggesting that this fungus is pathogenic to the weeds, and in part responsible for the brûlé, thanks to this apparent pathogenic effect and to the production of toxic volatiles. Since the inhibitory effect of T. melanosporum volatiles on herbaceous plants has been widely acknowledged ( Splivallo et al, 2007, Splivallo et al, 2011and Streiblova et al, 2012, which would seem to indicate that fungal volatiles can mediate fungal-plant interactions, it is possible to imagine that there could also be an effect of T. melanosporum on the AMF that colonize the patchy vegetation. This work clearly shows, for the first time, that the patchy herbaceous plants around a T. melanosporum host tree are colonized by AMF to a great extent, as are the plants outside the brûlé, where the vegetation coverage is regular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A close correlation between infection in herbaceous plant roots and Tubermelanosporum was observed by Plattner & Hall (1995), who demonstrated that T. melanosporum caused necrosis in the root cortices of Anthoxanthum odoratum, and Leontodon taraxacoides, thus suggesting that this fungus is pathogenic to the weeds, and in part responsible for the brûlé, thanks to this apparent pathogenic effect and to the production of toxic volatiles. Since the inhibitory effect of T. melanosporum volatiles on herbaceous plants has been widely acknowledged ( Splivallo et al, 2007, Splivallo et al, 2011and Streiblova et al, 2012, which would seem to indicate that fungal volatiles can mediate fungal-plant interactions, it is possible to imagine that there could also be an effect of T. melanosporum on the AMF that colonize the patchy vegetation. This work clearly shows, for the first time, that the patchy herbaceous plants around a T. melanosporum host tree are colonized by AMF to a great extent, as are the plants outside the brûlé, where the vegetation coverage is regular.…”
Section: Discussionmentioning
confidence: 99%
“…( Pacioni 1991). Splivallo et al (2007) have demonstrated the inhibitory effect of truffle volatiles on the development of the nonhost plant Arabidopsis thaliana in laboratory conditions, and have indicated that fungal volatiles are molecules that can mediate fungal-plant interactions, thus raising questions about their role in the origin of the brûlé. In addition, truffle mycelia produce ethylene and indole-3-acetic acid (IAA), which, in large quantities, might act as herbicides and thus explain the formation of the brûlé ( Splivallo et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The PGP effects were largely attributed to two volatiles, namely, 3-hydroxybutan-2-one (acetoin) and 2,3-butanediol. Several other studies have examined bacterial bioactive volatile compounds that promote or suppress plant growth (Farag et al, 2006;Splivallo et al, 2007;Vespermann et al, 2007;Kai et al, , 2010Gutiérrez-Luna et al, 2010;Zou et al, 2010;Blom et al, 2011aBlom et al, , 2011bVelazquez-Becerra et al, 2011;Weise et al, 2012;Yu and Lee, 2013), but the underlying mechanisms of these effects remain largely unknown (Wenke et al, 2012b). Profiling studies in Arabidopsis seedlings provided the first insights into changes in the transcriptome and proteome elicited by exposure to bacterial VOCs (Zhang et al, 2007;Kwon et al, 2010) and revealed the importance of hormone signaling, particularly that of indole-3-acetic acid and abscisic acid (Zhang et al, 2007(Zhang et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Volatile organic compounds have been implicated in the signaling between truffle and plants. Splivallo et al (2007) discussed the phytotoxic activity of fruiting body volatiles and Menotta et al (2004) highlighted their potential role as mycorrhization signals. Fruiting bodies volatiles shortened primary roots of plants (Splivallo et al, 2007) while the effect of mycelial metabolites has not been addressed.…”
mentioning
confidence: 99%